2011
DOI: 10.1093/cid/cir619
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft Cytomegalovirus Protein Expression Is Associated With Reduced Renal Allograft Survival

Abstract: We provide evidence that intragraft CMV protein expression is associated with end-stage chronic renal allograft dysfunction, that intragraft CMV levels increase as graft function deteriorates, and that CMV protein expression in the grafts soon after transplant is associated with reduced graft survival. Thus, CMV may have a pathological role in chronic renal allograft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 199 publications
(214 reference statements)
1
42
1
3
Order By: Relevance
“…CMV has multiple additional survival strategies that target hosts' adaptive and innate immune functions, that diminish mobilization of phagocytes and antigen presentation, and that produce homologs of host cytokine and chemokine receptors (1-7); however, the mechanisms linking CMV infection with diminished graft function are incompletely understood (8). CMV infections of grafts cause what have been termed "direct effects" in the allograft, including inflammation, vasculopathy and fibrosis with resultant chronic allograft dysfunction (9)(10)(11)(12). "Indirect effects," or systemic effects beyond those attributable to direct viral injury, are mediated by upregulation of specific T and B cell alloimmune responses by innate immune mechanisms (inflammatory mediators, mobilization of antigenpresenting cells with improved antigen presentation, diminished regulatory responses) or by stimulation of alloimmunity by cross-reactive viral antigens with resultant graft injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV has multiple additional survival strategies that target hosts' adaptive and innate immune functions, that diminish mobilization of phagocytes and antigen presentation, and that produce homologs of host cytokine and chemokine receptors (1-7); however, the mechanisms linking CMV infection with diminished graft function are incompletely understood (8). CMV infections of grafts cause what have been termed "direct effects" in the allograft, including inflammation, vasculopathy and fibrosis with resultant chronic allograft dysfunction (9)(10)(11)(12). "Indirect effects," or systemic effects beyond those attributable to direct viral injury, are mediated by upregulation of specific T and B cell alloimmune responses by innate immune mechanisms (inflammatory mediators, mobilization of antigenpresenting cells with improved antigen presentation, diminished regulatory responses) or by stimulation of alloimmunity by cross-reactive viral antigens with resultant graft injury.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies have indicated that successful antiviral prophylaxis has a beneficial effect on long-term graft function (8). This suggests that viral replication is a component of risk, but the precise mechanisms underlying this effect are debated (9,11,(26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent CMV infection measured by immunohistochemistry in the allograft biopsy of kidney transplant recipients was associated with increased expression of TGF-b and PDGF in the tubule and vascular endothelium (43), these molecules being directly involved in the pathogenesis of CAN. Intra-allograft CMV protein expression correlated with the development of chronic allograft dysfunction in a small series of kidney transplant recipients (44). Moreover, in in vitro models, CMV upregulated the expression of IL-8 in fibroblasts; this major mediator of the inflammatory response may play a role in the pathogenesis of bronchiolitis (23).…”
Section: Viral Infections and Chronic Allograft Dysfunctionmentioning
confidence: 99%
“…In renal transplant recipients, CMV infection has been related to acute rejection and chronic allograft dysfunction (36,44,65,66). In a retrospective cohort study, 2740 kidney and simultaneous pancreas-kidney transplants were analyzed to evaluate the strength of acute rejection and CMV disease as risk factors for allograft loss.…”
Section: Type Of Organ Transplantmentioning
confidence: 99%
“…Only one in four adults (black or white) living below the 200% poverty level have health insurance. 1,2 In this issue of JASN, Grams et al examine the effect of race on the incidence of AKI-related hospitalizations. 3 They used selfidentified black and white participants from the Atherosclerosis Risk in Communities (ARIC) study.…”
Section: President Barack Obama 2007 Iowa Brown and Black Presidentialmentioning
confidence: 99%